2001
DOI: 10.1007/s004410100363
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor-α and -β immunoreactivity and mRNA in neurons of sensory and autonomic ganglia and spinal cord

Abstract: Estrogen receptor-alpha immunoreactivity and mRNAs are present in neurons in locales that innervate genital organs, e.g., parasympathetic pelvic autonomic ganglia, sensory dorsal root and nodose ganglia, and autonomic areas of the lumbosacral spinal cord. With the availability of probes for the beta-isoform of the estrogen receptor, we studied this receptor in autonomic, sensory, and spinal cord neurons and compared it with the distribution of the alpha-receptor. Estrogen receptor-alpha and -beta immunoreactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
120
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(137 citation statements)
references
References 110 publications
16
120
1
Order By: Relevance
“…The gastrointestinal tract is highly innervated, and primary sensory afferents convey information between intestine and central nervous system, adapting nociceptive behavior. Estrogen receptors are widely expressed throughout the sensory processing pathway, including dorsal root ganglia and spinal cord (36,37). Our study showed that BPA induces visceral hypersensitivity to graded intensities of colorectal distension, an effect blocked by ICI 182.780, thus depending on ER binding activity.…”
Section: Discussionmentioning
confidence: 55%
“…The gastrointestinal tract is highly innervated, and primary sensory afferents convey information between intestine and central nervous system, adapting nociceptive behavior. Estrogen receptors are widely expressed throughout the sensory processing pathway, including dorsal root ganglia and spinal cord (36,37). Our study showed that BPA induces visceral hypersensitivity to graded intensities of colorectal distension, an effect blocked by ICI 182.780, thus depending on ER binding activity.…”
Section: Discussionmentioning
confidence: 55%
“…The sex differences in the distribution pattern are minor (Burke et al, 2000;Vanderhorst et al, 2005). The other known estrogen receptor, ER, is present in laminae II-III in the spinal cord and trigeminal subnucleus caudalis, as shown in female rats (Papka et al, 2001;Shughrue et al, 1997) but the number of cells is small and the mRNA expression is low. Putative membrane ERs, such as GPR30, are also expressed in the rat spinal dorsal horn and dorsal root ganglia (Brailoiu et al, 2007;Dun et al, 2009;Takanami et al, 2010).…”
Section: The Characteristics Of Spinal Er-neurons and Their Relatiomentioning
confidence: 93%
“…6 The nuclei of sensory neurons innervating the uterus are known to express ERs, 15 and ER-dependent signaling modulates a range of processes in peripheral nerves. 29,30 We were, therefore, interested in exploring whether the estrogen-dominated microenvironment could play a role in modulating interactions between macrophages and nerves and what regulatory factors may be involved.…”
Section: E2 Mediates a Two-way Dialogue Between Macrophages And Nervesmentioning
confidence: 99%
“…14 Notably, a proportion of the soma of afferent nerve fibers innervating the uterus and peritoneum is reported to express one or both ERs. 15 Although some studies have analyzed the expression of ERs in macrophages isolated from the peritoneal fluid of women with endometriosis, 16,17 expression of ERs in lesion-resident macrophages has not yet been determined.…”
mentioning
confidence: 99%